Role Model Pembelajaran Sebagai Sarana Inovatif Pembelajaran Jarak Jauh Di Masa Pandemi Covid 19 - Muwahhidah Nurhasanah (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2020)
Role playing method is a method of learning that involves students to be active and students play an important role in learning. The use of this role playing method can make the learning atmosphere more enjoyable so as to motivate students and students to become enthusiastic during learning. Each method certainly has its own weaknesses and advantages as well as this method of role playing learning, therefore a teacher or educator needs to combine this role playing learning with other methods in accordance with the material or competency standards that students want to achieve. Distance education is not a new method in the education system. Distance learning methods continue to evolve using a variety of communication and information technologies including radio, television, satellite, and internet. The widespread use of the internet by the public in various countries in 1996 became a growing phenomenon and was followed by the emergence of various digital content in it. Keyword : role model, learning, innovative, distance, COVID 19